2021
DOI: 10.3389/fimmu.2021.715582
|View full text |Cite
|
Sign up to set email alerts
|

Structure of African Swine Fever Virus and Associated Molecular Mechanisms Underlying Infection and Immunosuppression: A Review

Abstract: African swine fever (ASF) is an acute, highly contagious, and deadly infectious disease. The mortality rate of the most acute and acute ASF infection is almost 100%. The World Organization for Animal Health [Office International des épizooties (OIE)] lists it as a legally reported animal disease and China lists it as class I animal epidemic. Since the first diagnosed ASF case in China on August 3, 2018, it has caused huge economic losses to animal husbandry. ASF is caused by the African swine fever virus (ASFV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
67
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(87 citation statements)
references
References 90 publications
(240 reference statements)
1
67
0
Order By: Relevance
“…On the contrary, viruses have developed multiple strategies to resist host immune defenses, and counteract IFN signaling. ASFV encodes more than 150 polypeptides, which establish complex interactions with the host for the benefit of the virus in order to evade the host's defenses (1). However, currently, there is still a lack of information regarding the roles of the viral proteins in host cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, viruses have developed multiple strategies to resist host immune defenses, and counteract IFN signaling. ASFV encodes more than 150 polypeptides, which establish complex interactions with the host for the benefit of the virus in order to evade the host's defenses (1). However, currently, there is still a lack of information regarding the roles of the viral proteins in host cells.…”
Section: Discussionmentioning
confidence: 99%
“…African swine fever virus (ASFV), the causative agent of African swine fever (ASF) which is a contagious disease of domestic pigs and wild boar, has spread globally in recent years with serious economic consequences for the swine industry. ASFV contains a linear double-stranded DNA genome that varies in length from about 170 to 193 kb and encodes 150-200 viral proteins, including 68 structural proteins and more than 100 non-structural proteins (1). Monocyte-macrophages are the main target cells of ASFV (2).…”
Section: Introductionmentioning
confidence: 99%
“…ASFV infection has been shown to upregulate the expression of immunosuppressive cytokines to put a strain on the host immune response. Previous studies have shown that IL27 , a suppressor of the immune response of Th1 and Th17 cells, is downregulated during ASFV infection [ 127 ]. However, IL27 was significantly upregulated in our study by over 2-fold in the medium and high dose groups.…”
Section: Discussionmentioning
confidence: 99%
“…ASFV has evolved the ability to manipulate host immune responses by encoding many immune escape genes, including regulation of IFN expression, inhibition of autophagy, and apoptosis. In addition, ASFV affects the antigen presentation and activation of lymphocytes by invading monocytes-macrophages and DCs, thereby affecting the immune system of the entire body [ 31 ]. This review summarizes the escape mechanism of ASFV from the immune response and the progress of ASF vaccines, hoping to provide help for future ASF vaccines research.…”
Section: Introductionmentioning
confidence: 99%